2014
DOI: 10.1016/j.jeurceramsoc.2013.12.026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phase formation during use on the chemical corrosion of magnesia–chromite refractories in contact with a non-ferrous PbO–SiO2 based slag

Abstract: One of the main factors limiting the lining lifetime in pyrometallurgical smelters is continuous refractory oxides dissolution in the slag bath. The overall wear is accelerated when the slag infiltrates the porous brick and the dissolution thus occurs in a larger part of the lining. This work investigates the possibility of preventing deep infiltration by sealing off the pores with newly formed phases. Static finger tests at constant temperature (1200 °C) were performed in contact with a synthetic nonferrous P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…An increase in the loss of ignition on samples DR2000 IN and DALMAG IN is apparently due to the infiltration of silicate phases through the layers of refractories while for D R2000 IN used in the zone of cooling; we observed an increase in percentage of silica and alumina due to the slag phases of the matter infiltrated through the pores of refractory. This result is agrees with previous published results [10,12]. For the sample DALMAG IN used in the clinkerisation zone, an increase on the percentages of alkaline elements K 2 O (+2.03), P 2 O 5 (+2.10), SO 3 (+2.10), and of Na 2 O (+2.32) is observed, these alkaline compounds are very aggressive for refractory bricks, they are basic elements from ashes of used coal combustion in the cement kiln.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…An increase in the loss of ignition on samples DR2000 IN and DALMAG IN is apparently due to the infiltration of silicate phases through the layers of refractories while for D R2000 IN used in the zone of cooling; we observed an increase in percentage of silica and alumina due to the slag phases of the matter infiltrated through the pores of refractory. This result is agrees with previous published results [10,12]. For the sample DALMAG IN used in the clinkerisation zone, an increase on the percentages of alkaline elements K 2 O (+2.03), P 2 O 5 (+2.10), SO 3 (+2.10), and of Na 2 O (+2.32) is observed, these alkaline compounds are very aggressive for refractory bricks, they are basic elements from ashes of used coal combustion in the cement kiln.…”
Section: Discussionsupporting
confidence: 94%
“…These compounds can contribute to the reduction of the basic element of bricks, the magnesia (%MgO: from 70,57 in ALMAGN to 50,12 in DALMAGIN), and by consequence a reduction in the resistance of bricks, As a remark, this results, deduced here, is the same obtained by [11] The degradation of brick of the aluminous-slice type (R2000) is characterized by the partial destruction of the phases Al 4 SiO 4 , and Silicates tricalcic Ca 3 SiO 5 of the clinker which are also infiltrated through the intrados of the bricks, this is in agreement with , SCHEUNIS and all. [12] who observed that the reaction between the refractory sample and the in¿ltrating liquid leads to the formation of new phases. This degradation in these two refractory bricks was primarily due to the dissolution of the spinel which involves a reduction in the resistance of refractory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 A general overview of wear phenomena in the lead melting furnaces is given in several papers. [5][6][7][8] Particularly in the lead industry, many investigations were done regarding refractory corrosion testing in different pilot-scale and industrial furnaces. For instance, Prestes et al 5 analyzed wear phenomena on magnesia-chromite bricks from a lead short rotary furnace.…”
Section: Introductionmentioning
confidence: 99%
“…Wei 6 reviewed the available literature concerning corrosion of refractories in lead-smelting reactors such as KIVCET furnace and top blowing rotary converter (TBRC), and then the corrosion behavior of various refractory materials in contact with industrial slags was evaluated in the laboratory. Finally, Scheunis et al 7 investigated the effect of phase formation during use on chemical corrosion of magnesia-chromite refractories in contact with PbO-SiO 2 -based slag from nonferrous metal production.…”
Section: Introductionmentioning
confidence: 99%